1994
DOI: 10.1126/science.8171341
|View full text |Cite
|
Sign up to set email alerts
|

Neural Tuning for Sound Duration: Role of Inhibitory Mechanisms in the Inferior Colliculus

Abstract: Duration is a biologically important feature of sound. Some neurons in the inferior colliculus of the big brown bat, Eptesicus fuscus, are tuned to sound duration, but it is unclear at what level the tuning originates or what neural mechanisms are responsible for it. The application of antagonists of the inhibitory neurotransmitters gamma-aminobutyric acid or glycine to neurons in the inferior colliculus eliminated duration tuning. Whole-cell patch-clamp recordings of synaptic currents suggested that inhibitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
283
5
3

Year Published

1996
1996
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 372 publications
(308 citation statements)
references
References 24 publications
17
283
5
3
Order By: Relevance
“…Neurons tuned for the duration of a stimulus have been found in the central auditory systems of a number of vertebrates, including frogs (Potter, 1965;Narins and Capranica, 1980;Hall and Feng, 1986;Gooler and Feng, 1992), mice (Brand et al, 2000), chinchillas (Chen, 1998), cats , and various species of echolocating bats (Jen and Schlegel, 1982;Pinheiro et al, 1991;Casseday et al, 1994;Condon et al, 1996;Galazyuk and Feng, 1997;Fuzessery and Hall, 1999). Neurons tuned to the duration of a stationary bar of light have also been found in areas 17 and 18 of the cat visual cortex (Duysens et al, 1996).…”
Section: Discussionmentioning
confidence: 95%
“…Neurons tuned for the duration of a stimulus have been found in the central auditory systems of a number of vertebrates, including frogs (Potter, 1965;Narins and Capranica, 1980;Hall and Feng, 1986;Gooler and Feng, 1992), mice (Brand et al, 2000), chinchillas (Chen, 1998), cats , and various species of echolocating bats (Jen and Schlegel, 1982;Pinheiro et al, 1991;Casseday et al, 1994;Condon et al, 1996;Galazyuk and Feng, 1997;Fuzessery and Hall, 1999). Neurons tuned to the duration of a stationary bar of light have also been found in areas 17 and 18 of the cat visual cortex (Duysens et al, 1996).…”
Section: Discussionmentioning
confidence: 95%
“…LG cells are shown to send long‐range projection to thalamus to elicit inhibitory response faster than excitation (Peruzzi, Bartlett, Smith, & Oliver, 1997). The long‐range connection inside the IC may also cause fast inhibition, which is important for coding complex information such as duration (Casseday et al., 1994). To understand the roles of local neurons on the synaptic‐domain‐based information coding, cell‐type specific manipulation of local circuit is required.…”
Section: Discussionmentioning
confidence: 99%
“…Lower brainstem nuclei, namely, cochlear nuclei (CN), SOC, and nuclei of the lateral lemniscus (NLL), analyze specific features of sound and send the analyzed information to the inferior colliculus (IC), which is the largest nuclei in entire subcortical auditory system (Ito, Bishop, & Oliver, 2016). Since all the sound information is converged, the IC is considered to integrate sound information and create coding of complex sound information: In bats, analyses related to echolocation such as tunings of sound duration (Casseday, Ehrlich, & Covey, 1994), and delay coding (Portfors & Wenstrup, 1999) are found in the IC.…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed that duration-selective neurons are present in early sensory areas for both auditory and visual information (Heron et al, 2012). Evidence for this claim comes from single cell recording studies in different mammals that have reported duration-selective neurons in both early auditory processing areas such as inferior colliculus and the auditory midbrain (Brand, Urban, & Grothe, 2000;Casseday, Ehrlich, & Covey, 1994;Ehrlich, Casseday, & Covey, 1997;He, Hashikawa, Ojima, & Kinouchi, 1997), as well as early visual areas such as area 17 & 18 (Duysens, Schaafsma, & Orban, 1996;Eriksson, Tompa, & Roland, 2008). One can argue that an early locus for duration processing can be beneficial given that the temporal integration window of neurons is known to increase along the visual processing hierarchy (Hasson, Yang, Vallines, Heeger, & Rubin, 2008).…”
Section: Introductionmentioning
confidence: 98%